A RARELY USED SOURCE FOR THE “PHONEY WAR”. THE SECRET FRENCH DOCUMENTS FOUND BY GERMAN SOLDIERS AT LA CHARITÉ-SUR-LOIRE ON JUNE 19TH, 1940 - Lars BAERENTZEN (Romanian Intelligence Studies Review, 2022)
Germany justified the April 9, 1940, attack on Norway and Denmark by claiming that Great Britain and France were planning an intervention in Scandinavia. After the defeat of France, German soldiers found on June 19, 1940, by chance, in abandoned railroad cars in La Charité-sur-Loire, many French secret documents which Berlin saw as a confirmation of this claim. The German Foreign Ministry in 1941 published 70 of these documents in Denmark and in other occupied countries including France. These texts were used in press articles and in some official speeches. This paper describes the circumstances of the capture and argues that the documents are genuine and may, with caution, be used as historical evidence, although the 1941 publication was indeed propaganda. A small number of the documents are presented in some detail. The German publication has apparently not been used by Danish historians, but a few post-war historians in Great Britain, the USA, France and Germany have made use of the “captured French documents” and have discussed their historical value. This paper argues that they are important for understanding the course of the war in early 1940, the period known as “The Phoney War”.